HUBUNGAN ANTARA MPV (MEAN PLATELET VOLUME) DENGAN LUAS INFARK MIOKARD PADA PASIEN STEMI (ST-SEGMENT ELEVATED MYOCARDIAL INFARCTION) YANG DIUKUR BERDASARKAN SKOR QRS SELVESTER - Bagus Kantwa Abhimantra, Gede; Rahmat, Basuki; Pintaningrum, Yusra (E-Jurnal Medika Udayana; Vol 11 No 7 (2022): E-Jurnal Medika UdayanaDO - 10.24843/MU.2022.V11.i7.P13, 2022)
Background : Globally heart disease occupy the first order of mortality population in the world. Acute myocardial infarction is one of them, in its classification AMI can be divided into STEMI and NSTEMI. Pathological changes in AMI will involve many things, one of them is platelets. The aim of the study is to know the correlation between Mean Platelet Volume (MPV) and the myocardial infarction size in STEMI patient based on QRS Selvester score. Methods: This study was an observational analytic study with a cross sectional approach. This research was conducted in July 2020-March 2021 at the Rumah Sakit Umum Kota Mataram, involving 63 subjects. Data obtained from patient medical records using non-probability sampling technique which is consecutive sampling. Results: From 63 data, there are 50 male patients and 13 female patients, the average of the patients age is 57.97 years old. MPV mean is 8.77 fL and the mean of myocardial infarction size is 25.33%. The data scale of the two variables is numerical for MPV and numerical for the myocardial infarction size. The normality test was performed using the Kolmogorov-Smirnov test and the MPV significance value was 0.200 and the myocardial infarction size was 0.200 (normal distribution). Pearson correlation test results obtained p=0.885 (p> 0.05). Conclusion: There is no significant correlation between the MPV and the myocardial infarction size.